The Role of Molybdenum in Biological Nitrogen Fixation - ., Armiadi (Indonesian Animal Sciences Society, 2009)
The availability of soil Molybdenum (Mo) especially for acid soil is scarcely found, while their existency determines the process of Nitrogen fixation. Mo is the component of meta-protein nitrogenase which helps the process of biological nitrogen fixation and acts as essential component which needed for N bacteria metabolism. The nitrogenase enzyme needs Mo element in the process of its metabolism, which acts as electron carrier between oxidized and reduction stages. The deficiency of Mo has been reported in several crops, with various appearance, such as chlorosis or yellowish leaves. The paper describes the role of Mo in biological nitrogen fixation. Â Key words: Symbiotic fixation, molybdenum, legume, nitrogenase